PENYEBARAN VIRUS RANSOMWARE WANNACRY BERDASARKAN UNDANG-UNDANG NO. 11 TAHUN 2008 - Irfan Arief Kurniawan; Hadi Mahmud; Nourma Dewi (Jurnal Inovasi Penelitian, 2021)
This study aims to find and describe the legal provisions for perpetrators of the crime of spreading computer viruses. analyze how the law is enforced against the perpetrators of the spread of computer viruses regulated in Law Number 11 of 2008. This study uses a method of normative legal approach to law enforcement against the perpetrators of the spread of computer virus wannacry ransomware based on Law No. 11 of 2008 concerning Information and Electronic Transactions. Data was collected by reviewing legal materials which were then analyzed using qualitative analysis techniques and interpreted logically and systematically and then drawn conclusions. Law enforcement against the perpetrators of the spread of computer viruses Ransomware wannacry, among others by prosecuting law by observing jurisdiction and applicable law, because in this case it is possible for the perpetrator to be in a country different from the country where the victim of this crime is located, besides, it is difficult to determine the place events (locus delicti) because these crimes occur in cyberspace. The perpetrators of the spread of computer viruses through Ransomware wannacry viruses can be subject to Article 46 paragraph (2) in conjunction with Article 30 paragraph (2) of the ITE Law. Law No. 11 of 2018 concerning ITE regulates and explains various actions for violating the law in the misuse of Information Technology. The spread of computer viruses Wannacry Ransomware is one of the prohibited acts as regulated in Article 30 paragraph (2) of the ITE Law, because in this case the virus contained in the computer component is considered as electronic information and / or documents that can be used as one of the evidence as stipulated in article 5 paragraph (1) and (2) of the ITE Law. Thus, the act of spreading computer viruses can be charged under Article 46 paragraph (2) in conjunction with Article 30 paragraph (2) of the ITE Law